2013
DOI: 10.1515/ijamh-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain in an eating disorders day program

Abstract: The data showed that most patients accomplished modest weight gains during a relatively short stay in an eating disorders day program, demonstrating what can be expected for this level of care in the current healthcare environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…As such, the magnitude of the influences of WS and BMI on weight change reported in the current study may be smaller at lower levels of care, once the behavioral factors are allowed to have a more pronounced effect. However, as prior research has found similar effects of WS and on weight gain in outpatient treatment samples (Carter et al, 2015;Carter, McIntosh, Joyce, & Bulik, 2008), the current results could potentially apply to various levels of care. Additionally, the lack of a standardized interview-based diagnostic system and reliability checks for the diagnoses given to patients is a weakness of the study.…”
Section: Bn Subgroupsupporting
confidence: 55%
See 1 more Smart Citation
“…As such, the magnitude of the influences of WS and BMI on weight change reported in the current study may be smaller at lower levels of care, once the behavioral factors are allowed to have a more pronounced effect. However, as prior research has found similar effects of WS and on weight gain in outpatient treatment samples (Carter et al, 2015;Carter, McIntosh, Joyce, & Bulik, 2008), the current results could potentially apply to various levels of care. Additionally, the lack of a standardized interview-based diagnostic system and reliability checks for the diagnoses given to patients is a weakness of the study.…”
Section: Bn Subgroupsupporting
confidence: 55%
“…Although WS has been repeatedly implicated as a predictor of weight gain in individuals with EDs (Herzog et al, ; Witt et al, ), including during treatment (Lowe et al, ), its predictive power remains an influence that neither patients nor providers appear fully aware of. Despite numerous treatment studies showing substantial variability in weight outcomes in patients with EDs (deGraft‐Johnson, Fisher, Rosen, Napolitano, & Laskin, ; Jennings, Gregas, & Wolfe, ; Pacanowski et al, ), there is very little clinical guidance for practitioners and patients regarding the implications of each patient's WS level for their susceptibility to weight gain in the future. To the extent that a major goal of treatment is to stabilize weight and eating patterns, failing to understand and acknowledge the differential expected weight trajectories based on current and past weights may run counter to the therapeutic goals.…”
Section: Discussionmentioning
confidence: 99%
“…Weight in all studies improved over the course of day treatment. Weight gain was correlated with a diagnosis of AN or EDNOS (versus BN), longer length of stay and lower weight at admission [261]. The length of stay in these studies varied between 15.3 weeks and 13.1 weeks.…”
Section: Day Treatment Multimodal Day Treatmentmentioning
confidence: 93%
“…Mixed diagnoses Several studies address mixed diagnoses of eating disorders within a multimodal day hospital program [257][258][259][260][261] (Table 55). Weight in all studies improved over the course of day treatment.…”
Section: Day Treatment Multimodal Day Treatmentmentioning
confidence: 99%
See 1 more Smart Citation